KAJIAN MOTIF BATIK GONGGONG CV LAWANA DI TANJUNG PINANG - Nancy Hanna Lumban Gaol (Institut Seni Indonesia Surakarta, 2022)
Gonggong CV Lawana in Tanjung Pinang using a textile design method approach. This research is formulated in one question